Traditional hand embroidery for wedding dress in Saudi Arabia: Makka and Madina / Daliah Abdulghader Fairak - Abdulghader Fairak, Daliah (2013)
There have been a number of researches that presented information on the history of traditional hand embroidery wedding dress of the people in Makkah and Madinah, which is a way to preserve the heritage and to renew it. This study also intends to demonstrate what today’s brides desire to wear, and also describe the methodology of collaborating the traditional hand embroidery with contemporary design. This study was conducted in order to identify certain aspects of young brides’ personality as a factor for implementing special gown design. By using the existing knowledge of the elders from Makkah and Madinah on the traditional hand embroidery and feedbacks from young brides, it is found that majority of them do not have the knowledge and understanding of the hand embroidery heritage. Moreover, a theoretical analysis backed by observations from Makkah and Madinah’s wedding dress shops, and Hejaz wedding ceremonies, indicates that young brides are attracted to the unique gown designs, such as traditional dresses that express their character. Quantitative results in the form of questionnaires are provided as evidence to show that modem gown designs embroidered with traditional hand embroidery is preferred by the young brides, who are responded to the questionnaire, and it also shows that it is feasible as a fashion item and is marketable in Makkah and Madinah’s clothing stores. The final results showed that a large number of the respondents agreed with this concept of integrating contemporary gown with traditional hand embroidery, while only small groups of them disagreed. However, from these small groups, little number disagreed based on the reason that they do not have enough facts about this handicraft. It is believed that this concept the integrating contemporary design with traditional hand embroidery will benefit the Saudi’s fashion industry, as well as a big step towards reviving wedding dress traditions and enhancing its productivity.